The impact of age and high‐risk human papillomavirus (hrHPV) status on the prevalence of high‐grade cervical intraepithelial neoplasia (CIN2+) in women with persistent hrHPV‐positive, cytology‐negative screening samples: a prospective cohort study. (3rd May 2020) - Tidy, JA; Lyon, R; Ellis, K; Macdonald, M; Palmer, JE
Abstract : Objective: To establish the prevalence of high‐grade cervical intraepithelial neoplasia (CIN2+) in women referred to colposcopy with persistent high‐risk human papillomavirus (hrHPV) cytology‐negative screening sample according to hrHPV genotype, age at referral and colposcopic performance. Design: Prospective cohort study. Setting: Single colposcopy clinic linked to a population‐based screening programme. Population: Women referred with persistent hrHPV cytology‐negative routine screening samples. Methods: Prospective study with descriptive statistics from a single colposcopy unit between June 2014 and July 2019. Main outcome measures: Prevalence of hrHPV genotypes and CIN2+, positive predictive value for colposcopic impression, and inadequate colposcopic examinations. Results: A total of 3107 women were referred. Prevalence of CIN2+ was highest for persistent HPV16 infections (10.7%) compared with HPV18 (3.6%) or HPVO (4.7%). Prevalence of CIN2+ declined with age (25–34 years 14.2% to 55–64 years 1.1%) whereas the percentage of women with an inadequate colposcopic examination increased (25–34 years 0.9% to 55–64 years 29.5%). High‐grade colposcopic impression fell over time during the study from 16.1 to 5.1%. The positive predictive value for colposcopic impression of CIN2+ was affected by hrHPV genotype (57.3% for HPV16 versus 32.1% for nonHPV16). The adjunctive use of electrical impedance spectroscopy detected an extra 42 cases of CIN2+, which was irrespective of hrHPV genotype. Conclusions: Primary hrHPV cervical screening increases detection of CIN2+; however, low specificity results in more women being referred to colposcopy with a low prevalence of CIN2+. Colposcopy performs poorly in some groups, particularly with HPVO infections and women over 50 years of age. An appropriate threshold for referral to colposcopy in primary hrHPV screening has not been established. Tweetable abstract: Low prevalence of CIN2+ in HPV‐positive negative cytology samples. HPV genotype, age and prevalence of CIN2+ affect colposcopic performance. Tweetable abstract: Low prevalence of CIN2+ in HPV‐positive negative cytology samples. HPV genotype, age and prevalence of CIN2+ affect colposcopic performance.